Performance analysis of indirect sCO₂ cycle integrated with different heat sources and thermal energy storage. - Thanganadar, Dhinesh (Cranfield University, 2020)
Increasing the efficiency of the power conversion cycles are crucial in order to reducing global carbon emission. Supercritical carbon dioxide (sCO₂) cycles can achieve higher efficiency than steam Rankine cycle at higher turbine inlet temperatures (>550 °C) with a compact plant footprint (up to tenfold). This PhD study focused on investigating the thermodynamic performance of sCO₂ cycle configurations for three different heat sources: coal-fired, natural gas and concentrated solar power (CSP) plants. The proposed configurations have not only increased the efficiency compared with the state-of-the-art power cycle but also shows cost reduction potential for some heat sources. ❖ For natural gas based combined cycle power plant, the efficiency of the novel sCO₂ cascade cycle has increased by 1.4%pts compared to a triple-pressure steam Rankine cycle (base case efficiency is 58.4% LHV) for a commercial SGT5-4000F gas turbine. The CO₂ emission is reduced by 26,774 tons/year (2.3%). ❖ The proposed novel sCO2 cycle configuration increases the efficiency of coal-fired power plant has increased by 3-4%pts compared to the state-of-the-art NETL baseline steam Rankine cycle (B12A efficiency is 40.7% HHV). This corresponds to a reduction of 6-8% in the cost of electricity, however, this falls within the uncertainty range of the equipment cost functions. The increased efficiency reduces the CO₂ emission by 204,031 tons/year (6.4% reduction). ❖ For a concentrated solar power plant, the sCO2 cycle efficiency is increased by 3.8-7%pts compared to steam Rankine cycles and the novel proposed cycle can reduce the capital cost up to 10.8% compared to the state-of-the-art sCO₂ recompression cycle, which is equivalent to a reduction of about 12-26% compared with the steam Rankine cycle. The performance of sCO2 cycle is more sensitive to the variations in ambient temperature. In a CSP plant, operating the plant at high ambient temperatures, not only penalises the performance of the sCO₂ cycle (i.e., net power output and efficiency), but also the sensible heat storage capacity. For instance, the storage capacity reduces by 25% for a 13 °C increase of the ambient temperature from its design value (i.e., 42°C) when maximising the power cycle efficiency. Therefore, these effect on the levelised cost of electricity is investigated in detail, which guides the effect of different plant operating modes. The transient heat exchanger model informs that the first-order characteristic time of the recuperators is faster (20-90 secs) when using compact heat exchangers,indicating the potential of fast load ramping.
Keywords: sCO₂ cycle; combined cycle; coal-fired plant; CSP; thermal energy storage; mult-objective optimisation; techno-economic